Tahap Awal Seleksi Galur Murni Ercis (Pisum sativum L.) Populasi Lokal Boyolali dan Temanggung Berdasarkan Karakteristik Fisik Biji - Fildza Abidah; Darmawan Saptadi; Budi Waluyo (Department of Agronomy, Faculty of Agriculture, Brawijaya University, 2021)
Pea (Pisum sativum L.) is a nutritious and high-value vegetable. Plant cultivation and the selection of superior cultivars are two ways to increase pea production. One technique of plant breeding for improved varieties is to get some genotipes from local populations. The genetic potential of the pure line selection based on the physical features of the seeds is indicated agronomic and morphological variability. The purpose of this study is to investigate agronomic characteristics and heritability of pea lines developed based on physical seed selection in local population. This research used randomized block desig) consist 22 lines based on seed characteristics selection, which are 12 local lines from Boyolali and 10 local lines from Temanggung as a treatment and repeated three times. Research has been carried out on January 2019 to April 2019 and located at Abdulrachman Saleh Air Force Base Agricultural Experimental Green House, Malang. Agronomics characters that have medium variability are flowering day, length from stem to first pod, length of leaf, length between first and second pods, length of tendrils, length of stem, number of branches, number of bracts, number of seeds per plant, weight of dry pods, weight of dry seeds per pod, length of dry seeds, width of dry seeds, and weight of dry seeds per plant. The high heritability are found inflowering day, day to harvesting dry pods, and length of nodes.